Pengaruh Komunikasi Antara Orang Tua dan Anak dalam Munculnya Perilaku Bullying pada Remaja - Aling, Olivia Angelica Regina; Rahmadani, Indah Ayu; Fauzan, M Akbar (JURNAL HARMONI NUSA BANGSA, 2023)
The aim of the research in this case is to find out the causes of bullying behavior in teenagers and to find out how big the influence of communication between parents and children is so that it can trigger bullying behavior in children. The method used in this research is a qualitative method through interviews with community participants who know about bullying behavior. The results of this research conclude that communication between parents and children has a big influence on the emergence of bullying behavior in teenagers.